Prevalence of vaginal infection by candida subtypes in women with HIV compared to the control group and influence of immune status - Reda, Somaia; Spautz, Ana Cecília Pedriali Guimarães; Gil, Isabela; Kato, Maria Victoria Fujii; Coltro, Elizabeth Souza Frade; Azuma, Mariana Hiromi; Obialski, Viviane; De Carvalho, Newton Sérgio (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Vulvovaginal candidiasis (VVC), caused by Candida sp, may present with increased frequency and symptoms in immunocompromised patients, and there is concern about the diagnosis and adequate treatment of these patients. Objective: The aim of this study was to evaluate the prevalence of VVC compared to the immune status and species present in the microbiota of patients with HIV. Methods: This cross-sectional study was conducted from January 2017 to January 2018, including 97 women with HIV compared to a control group (n=112). For data collection, interviews were conducted, vaginal pH was measured, CD4+ T cells and viral load (VL) were evaluated, and vaginal secretions were collected for microscopy and culture. Results: The prevalence of VVC was 41.2% in seropositive patients and 3.6% in the control group (p<0.001). Of the patients with CD4+<200 T, 54.3% had Candida sp, while in those with CD4+ T ³200 cells/mm³, the prevalence was 33.9% (p=0.057). Regarding viral load, the prevalence of VVC was 24.1% in those with undetectable VL or <20, 50% in those with VL between 20 and 9999, and 46.9% in VL above 10000 copies/mL (p=0.08). The most prevalent species were Candida albicans, followed by C. parapsilosis, C. krusei, and C. glabrata. The mean vaginal pH was 4.6 in the control group and 5.2 in the case group. Conclusion: HIV-positive women have a higher prevalence of candida. Lower T CD4+ values and increased VL seem to be associated with a higher prevalence of infection.